David Foote Sellers papers - Sellers, David Foote, 1874-1949.
Correspondence, memoranda, journals, notebooks, speeches, newspaper clippings, scrapbooks, photographs, and other papers relating to Sellers's naval career. Topics include his duty as cadet midshipman at the U.S. Naval Academy; his service during the Spanish-American War, the Samoan campaign, Philippine Insurrection, and World War I; as naval aide to the White House; as aide to the commander of the German fleet (Kriegsmarine) visiting the United States; his service relating to the Panama-Pacific International Exposition, San Francisco, Calif. (1915); as commander of the Naval Training Station at San Diego, Calif.; as commander-in-chief of the U.S. Navy Special Service Squadron; as commander-in-chief of the U.S. Navy U.S. Fleet; and as superintendent of the U.S. Naval Academy. Correspondence relates chiefly to his duty as commander of the U.S. Navy Special Service Squadron during the Nicaraguan uprising (1927-1929). Correspondents include Charles Francis Adams, Harry Alexander Baldridge, Hanson Weightman Baldwin, Richard Evelyn Byrd, Harold W. Dodds, Helen Keller, and Dudley Wright Knox.
Naval officer.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Forms part of: Naval Historical Foundation collection.
Keywords: Adams, Charles Francis, -- 1866-1954 -- Correspondence; Baldridge, Harry Alexander, -- 1880-1952 -- Correspondence; Baldwin, Hanson Weightman, -- 1903-1991 -- Correspondence; Byrd, Richard Evelyn, -- 1888-1957 -- Correspondence; Dodds, Harold W. -- 1889-1980 -- Correspondence; Keller, Helen, -- 1880-1968 -- Correspondence; Knox, Dudley Wright, -- 1877-1960 -- Correspondence; Germany. -- Kriegsmarine; United States. -- Naval Training Station (San Diego, Calif.); United States. -- Navy -- Officers; United States. -- Navy. -- U.S. Fleet; United States. -- Navy. -- Special Service Squadron; United States Naval Academy; Spanish-American War, 1898 -- Naval operations, American; World War, 1914-1918 -- Naval operations, American; Nicaragua -- History -- 1909-1937.; Philippines -- History -- Philippine American War, 1899-1902.; Samoa -- History; Naval officers